Self-catalyzed nanoscale ammonium perchlorate for advanced composite solid rocket propellant. (23rd September 2021) - Abdelhafiz, Mahmoud; Yehia, Mohamed; Mostafa, Hosam E; Wafy, Tamer
Abstract: Ammonium perchlorate (AP) is still one of the most important oxidizers used. Improving propellant output becomes an interesting source for many researchers. Due to its large surface area and high surface energy, nanomaterials have a wide range of applications in propellant formulations. High surface energy is responsible for the relatively low energy of activation and higher burning composition. This paper reports on a liquid-state method of synthesizing nanoscale AP. The resulting AP particles were characterized using electron scanning microscopy (SEM), energy dispersive x-ray spectrometer (EDX), x-ray diffraction (XRD), differential scanning calorimetry (DSC), and thermal gravimetric analysis (TGA). Kissinger and KAS techniques were used to measure the activation energy of nanoscale AP and microscale AP. The results showed that nanoscale AP possessed stronger catalytic activity than microscale AP where the temperature of decomposition fell from 452.8 °C to 388.1 °C and the heat released increased from 835.3 J g −1 to 3127 J g −1 . The findings of the kinetics study showed that the nanoscale of the synthesized AP has a direct effect on the activation energy of AP, where the activation energy of AP decreased from 226.0. kJ.mol −1 to 52.0 kJ.mol −1 .